Keine Experimente ! - Ayaal Herdam (Discours)
The rules of the « electoral slogans » genre, and specifically the need to present complex information in a striking manner, in few words, while also taking into account prosodic aspects and visual impact, mean that these small texts are particularly rich in verbless utterances. The corpus studied here – a collection of electoral slogans in German from the 1920s up to now – contains more than 50 % of utterances without a conjugated verb. Analysis shows that verbless utterances have become particularly frequent after 1970. The study proposes several ways to explain this tendency, from a general evolution of society to changes in the conception of electoral slogans, such as the substitution of the imperative by verbless options. The different classes of verbless utterances are investigated from a pragmatic position.